Compact Advanced Self-Study Pack. - Collectif (Cambridge University Press ELT, 2024)
Compact offers intensive revision and practice to quickly maximise student performance. With this course you will consolidate language and skills for exam success through clear, concise training. Compact helps you build confidence with its unique step-by-step approach and teaches essential exam strategies through user-friendly Exam tips. The exam-specific Grammar sections and Grammar reference deepen understanding of language structures, while the Speaking bank and Writing bank extend proficiency in productive skills. This Self Study pack gives you access to the Workbook eBook, Answer key, Grammar and vocabulary and exam practice all available online on Cambridge One.